1990
DOI: 10.1111/j.1365-3083.1990.tb03209.x
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Agarose Beads by Receptors for C3b (CR1) and iC3b (CR3) on Alveolar Macrophages from Patients with Sarcoidosis

Abstract: Alveolar macrophages (AM) from sarcoidosis patients exhibit no detectable defect in their potential to synthesize the functional alternative and terminal pathway of complement. They also synthesize more C9 than AM from healthy controls. Various authors have suggested that sarcoid AM have decreased phagocytic ability. In the present work we studied whether there was any difference in C3 receptor-mediated phagocytosis of serum-treated and native agarose beads by AM recovered from patients with active sarcoidosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It has been shown that the C3bi-mediated phagocytosis of agarose beads is dependent on CD1 lb [105]. The enhanced respiratory burst of the alveolar macrophages seen in sarcoidosis also depends on the expression of CDll/CD18 epitopes [115].…”
Section: Sarcoidosismentioning
confidence: 99%
“…It has been shown that the C3bi-mediated phagocytosis of agarose beads is dependent on CD1 lb [105]. The enhanced respiratory burst of the alveolar macrophages seen in sarcoidosis also depends on the expression of CDll/CD18 epitopes [115].…”
Section: Sarcoidosismentioning
confidence: 99%
“…Increases of C3a levels in BAL [34] and of complement synthesis by AMs have been observed [19,42]. Compared to normal controls, PET-TERSEN et al [43] found a higher expression of CR1 and CR3 and phagocytosis of AMs in patients with sarcoidosis stages I to III according to SILTZBACH [44]. In sarcoidosis, sCR1 correlated with the BAL lymphocyte count, suggesting a lymphocyte-dependent sCR1 production in this disease.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, increased CD lib expression on BAL macrophages is associated with disease activity in sarcoidosis, another frequent ILD [11], Similarly, an increased expression of surface mole cules of the CD11/CD18 family appears to be closely related with an exaggerated production of superoxide anions by these inflammatory cells [12]. Oxidant injury plays an important role in a number of human and experi mental acute and chronic lung disorders [13,14], There fore, the increased expression of CD 11 /CD 18 epitopes on macrophages obtained from injured lungs seems to be accompanied by changes in cell function, and for exam ple, it has been demonstrated that the C3bi-mediated phagocytosis of agarose beads is dependent on C D llb [15].…”
Section: Discussionmentioning
confidence: 99%